Comparative Effects of Pterostilbene and Its Parent Compound Resveratrol on Oxidative Stress and Inflammation in Steatohepatitis Induced by High-Fat High-Fructose Feeding - Saioa Gómez-Zorita; Maitane González-Arceo; Jenifer Trepiana; Leixuri Aguirre; Ana B Crujeiras; Esperanza Irles; Nerea Segues; Luis Bujanda; María Puy Portillo (MDPI AG, 2020)
Different studies have revealed that oxidative stress and inflammation are crucial in NAFLD (Non-alcoholic fatty liver disease). The aim of this study is to analyze whether pterostilbene and resveratrol are able to either avoid or delay the progression of non-alcoholic liver steatosis towards steatohepatitis. This has been performed by examining their effects on oxidative stress, inflammation, fibrosis and pre-carcinogenic stages. Rats were distributed into five experimental groups and were fed with either a standard diet or a high-fat high-fructose diet, supplemented or not with pterostilbene (15 or 30 mg/kg/d) or resveratrol (30 mg/kg/d), for 8 weeks. Liver histological analysis was carried out by haematoxylin-eosin staining. Serum and hepatic oxidative stress-related parameters were assessed using spectrophotometry, and the expression of genes related to inflammation, fibrosis and cancer by qRT-PCR. The dietary model used in this study led to the development of steatohepatitis, where rats displayed oxidative stress, inflammation and ballooning, although not fibrosis. It also modified the expression of hepatocarcinoma-related genes. The results show, for the first time, that pterostilbene was able to partially prevent these alterations, with the exception of changes in hepatocarcinoma-related genes, mainly at 30 mg/kg/d. Pterostilbene was more effective than its parent compound resveratrol, probably due to its high bioavailability and higher anti-oxidant and anti-inflammatory activities, attributable to its different chemical structure.